1998
DOI: 10.1523/jneurosci.18-08-03035.1998
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic α2C-Receptors Modulate the Acoustic Startle Reflex, Prepulse Inhibition, and Aggression in Mice

Abstract: Studies on animal models of stress, anxiety, aggression, and sensorimotor gating have linked specific monoamine neurotransmitter abnormalities to the cognitive and behavioral disturbances associated with many affective neuropsychiatric disorders. Although alpha2-adrenoceptors (alpha2-ARs) have been suggested to have a modulatory role in these disorders, the specific roles of each alpha2-AR subtype (alpha2A, alpha2B, and alpha2C) are largely unknown. The restricted availability of relevant animal models and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(108 citation statements)
references
References 46 publications
(56 reference statements)
5
98
1
4
Order By: Relevance
“…A few studies using transgenic mice have shown that mice lacking the a2C receptor have disrupted PPI (Sallinen et al, 1998) while mice lacking the a1D receptor or the a2A receptor do not show the same magnitude of disruption in PPI after psychotomimetic drug administration as wild-type mice (Lahdesmaki et al, 2004;Mishima et al, 2004). It must be pointed out though, that a recent study examined the effects of the a2 antagonist yohimbine on PPI and found that while yohimbine disrupts PPI, this effect may in part be due to its actions at serotonin-1A receptors (Powell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies using transgenic mice have shown that mice lacking the a2C receptor have disrupted PPI (Sallinen et al, 1998) while mice lacking the a1D receptor or the a2A receptor do not show the same magnitude of disruption in PPI after psychotomimetic drug administration as wild-type mice (Lahdesmaki et al, 2004;Mishima et al, 2004). It must be pointed out though, that a recent study examined the effects of the a2 antagonist yohimbine on PPI and found that while yohimbine disrupts PPI, this effect may in part be due to its actions at serotonin-1A receptors (Powell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ati had opposite effects on startle in a 2A -KO and WT mice, indicating that blockade of a 2A -AR mediates the startle-enhancing, anxiogenic-like effects of a 2 -AR antagonists. Considering the altered startle reflex and cortical arousal in mice lacking the a 2C -AR (Sallinen et al, 1998;Puoliväli et al, 2002), it is possible that the slight startle reduction by Ati in a 2A -KO mice is based on a 2C -AR blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several genetically altered mouse lines with modified expression of neurotransmitter receptors or transporters have been examined to investigate the potential genetic basis of sensorimotor gating (Geyer et al, 2002). Mouse strains reported to have increased basal PPI have included 5HT 1B -KO (Dulawa et al, 2000) and a 2C -overexpressing mice (Sallinen et al, 1998). It can be speculated that endogenous NE tonically reduces the level of PPI via a 2A -AR, and inactivation of the a 2A -AR gene thus results in increased PPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transgenic phenotypes make definition of the potential clinical applications of a 2C -selective ligands somewhat problematic. Thus, whereas a 2C knockout animals exhibit an 'antidepressant-like' profile in the forced swim test (FST) and overexpressing mice show a response consistent with greater learned helplessness in this paradigm (suggesting that a 2C -adrenoceptor antagonists have potential for treating stress-related disorders such as depression; Sallinen et al, 1999), data on prepulse inhibition of the auditory startle response (PPI) predict that a 2C -adrenoceptor agonism might be beneficial in situations where this response is impaired, such as schizophrenia (Sallinen et al, 1998a). a 2C -Adrenoceptor knockout mice also show hyper-responsiveness to amphetamine (Sallinen et al, 1998b), again consistent with the idea that an agonist might have antipsychotic properties.…”
mentioning
confidence: 99%